Forest-climate interactions in fragmented tropical landscapes - Laurance, William F. (Tropical Forests and Global Atmospheric Change, 2007)
In the tropics, habitat fragmentation alters forest-climate interactions in diverse ways. On a local scale (<1 km), elevated desiccation and wind disturbance near fragment margins lead to sharply increased tree mortality, altering canopy-gap dynamics, plant-community composition, biomass dynamics, and carbon storage. Fragmented forests are also highly vulnerable to edge-related fires, especially in regions which have periodic droughts or strong dry seasons. At landscape to regional scales (10-1,000 km), habitat fragmentation may have complex effects on forest-climate interactions, with important consequences for atmospheric circulation, water cycling, and precipitation. Positive feedbacks among deforestation, regional climate change, and fire could pose a serious threat for some tropical forests, but the details of such interactions are poorly understood. © The Royal Society 2005. All rights reserved.